On Estimation of Problems and Prospects of Competitiveness Growth on the World Market of Educational Services by Russian Higher Schools - V N Denisenko; L I Yefremova; G F Tkach (Peoples' Friendship University of Russia (RUDN University), 2013)
The analysis of the survey of the representatives of the Russian higher schools on the problems of the international educational cooperation and the participation in the international academic mobility is submitted in the article.